Effect of Economic Growth, Population to ZIS with Poverty in Aceh Province - Solawati Berasa; Kadimah Purnama Manik; Nurhalimah Boangmanalu; Asnidar (International Journal of Business and Applied Economics, 2023)
This study aims to determine the effect of economic growth and population on ZIS and poverty in Aceh Province in 2011–2020. This type of research is a quantitative study that uses secondary data obtained from BPS Aceh, namely data on economic growth, population, and poverty. and also taken from ZIS Aceh data (2011–2020). The data processor uses EViews 10. The results of this study indicate that there is no significant effect of the variables of economic growth and population on poverty. Economic growth has a significant influence on ZIS. There is no significant effect of population on zakat, infaq, and alms (ZIS).